The Artificial Sweetener Splenda Promotes Gut Proteobacteria, Dysbiosis, and Myeloperoxidase Reactivity in Crohn's Disease–Like Ileitis. Issue 5 (15th March 2018) - Rodriguez-Palacios, Alexander; Harding, Andrew; Menghini, Paola; Himmelman, Catherine; Retuerto, Mauricio; Nickerson, Kourtney P; Lam, Minh; Croniger, Colleen M; McLean, Mairi H; Durum, Scott K; Pizarro, Theresa T; Ghannoum, Mahmoud A; et al.
Abstract: Background: Epidemiological studies indicate that the use of artificial sweeteners doubles the risk for Crohn's disease (CD). Herein, we experimentally quantified the impact of 6-week supplementation with a commercial sweetener (Splenda; ingredients sucralose maltodextrin, 1:99, w/w) on both the severity of CD-like ileitis and the intestinal microbiome alterations using SAMP1/YitFc (SAMP) mice. Methods: Metagenomic shotgun DNA sequencing was first used to characterize the microbiome of ileitis-prone SAMP mice. Then, 16S rRNA microbiome sequencing, quantitative polymerase chain reaction, fluorescent in situ hybridization (FISH), bacterial culture, stereomicroscopy, histology, and myeloperoxidase (MPO) activity analyses were then implemented to compare the microbiome and ileitis phenotype in SAMP with that of control ileitis-free AKR/J mice after Splenda supplementation. Results: Metagenomics indicated that SAMP mice have a gut microbial phenotype rich in Bacteroidetes, and experiments showed that Helicobacteraceae did not have an exacerbating effect on ileitis. Splenda did not increase the severity of (stereomicroscopic/histological) ileitis; however, biochemically, ileal MPO activity was increased in SAMP treated with Splenda compared with nonsupplemented mice ( P < 0.022) and healthy AKR mice. Splenda promoted dysbiosis with expansion of Proteobacteria in all mice, and E. coli overgrowth with increased bacterial infiltration into the ileal lamina propria of SAMP mice. FISH showed increase malX gene–carrying bacterial clusters in the ilea of supplemented SAMP (but not AKR) mice. Conclusions: Splenda promoted gut Proteobacteria, dysbiosis, and biochemical MPO reactivity in a spontaneous model of ( Bacteroidetes -rich) ileal CD. Our results indicate that although Splenda may promote parallel microbiome alterations in CD-prone and healthy hosts, this did not result in elevated MPO levels in healthy mice, only CD-prone mice. The consumption of sucralose/maltodextrin-containing foods might exacerbate MPO intestinal reactivity only in individuals with a pro-inflammatory predisposition, such as CD.